2007
DOI: 10.1007/s11239-006-9015-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of ambulatory ECG (Holter) monitoring in patients with coronary heart disease: a review

Abstract: Silent ischemia, the most common expression of atherosclerotic heart disease, affects approximately 30-50% of patients during their activities of daily living. The present review provides a comprehensive and practical summary of current knowledge on perioperative myocardial ischemia through MEDLINE searches up to June 2005, using keywords including "silent ischemia," "transient ischemia," and "Holter monitoring." Holter monitoring (i.e., continuous ambulatory ST-segment monitoring) is an effective tool for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 59 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…In this cohort of patients, the great majority of myocardial infarctions occurred within the fi rst 3 days postoperatively (Badner et al 1998). It may be diffi cult to assess the true incidence of postoperative myocardial infarction, as it is dependent on the specifi city and sensitivity of the method of diagnosis (Gibson et al 2007), and the fact that some are silent clinically (Pasternack et al 1989). In a prospective study involving 444 patients with or at high risk for coronary artery disease who underwent elective noncardiac surgery, Mangano and colleagues (1992) found that postoperative myocardial ischemia increased the odds for long-term (30 days to 2 years after surgery) cardiac events (unstable angina, nonfatal myocardial infarction, cardiac death, surgical coronary revascularization) by 2.2-fold.…”
Section: Perioperative Cardiac Complicationsmentioning
confidence: 95%
“…In this cohort of patients, the great majority of myocardial infarctions occurred within the fi rst 3 days postoperatively (Badner et al 1998). It may be diffi cult to assess the true incidence of postoperative myocardial infarction, as it is dependent on the specifi city and sensitivity of the method of diagnosis (Gibson et al 2007), and the fact that some are silent clinically (Pasternack et al 1989). In a prospective study involving 444 patients with or at high risk for coronary artery disease who underwent elective noncardiac surgery, Mangano and colleagues (1992) found that postoperative myocardial ischemia increased the odds for long-term (30 days to 2 years after surgery) cardiac events (unstable angina, nonfatal myocardial infarction, cardiac death, surgical coronary revascularization) by 2.2-fold.…”
Section: Perioperative Cardiac Complicationsmentioning
confidence: 95%
“…In this cohort of patients, the great majority of myocardial infarctions occurred within the first 3 days postoperatively (Badner et al 1998). It may be difficult to assess the true incidence of postoperative myocardial infarction, as it is dependent on the specificity and sensitivity of the method of diagnosis (Gibson et al 2007), and the fact that some are silent clinically (Pasternack et al 1989). In a prospective study involving 444 patients with or at high risk for coronary artery disease who underwent elective noncardiac surgery, Mangano and colleagues (1992) found that postoperative myocardial ischemia increased the odds for long-term (30 days to 2 years after surgery) cardiac events (unstable angina, nonfatal myocardial infarction, cardiac death, surgical coronary revascularization) by 2.2-fold.…”
Section: Perioperative Cardiac Complicationsmentioning
confidence: 99%
“…Whereas in 40% of patients, the cause of syncope remains unknown after extensive clinical workup (5, 6). The disappointing results of ambulatory ECG monitoring are well known, since the heart rhythm of the patient is seldom monitored during an event (7, 8). The major difficulties to diagnosis are the unpredictable and uncommon nature of events and the high spontaneous recovery.…”
Section: Introductionmentioning
confidence: 99%